Integrating the value of natural capital in evidence-based policy making - Onil Banerjee; Renato Vargas; Martín Cicowiez (Inter-American Development Bank (IDB), 2020)
This paper describes how Natural Capital Accounting (NCA) can be integrated into economy wide analytical frameworks to enhance evidence based decision making. Examples from applications of the Integrated Environmental Economic Modelling (IEEM) Platform show how explicitly accounting for the contributions of the environment to the economy in economic forecasting can lead to substantially different policy recommendations, overcoming some of the scope limitations of traditional economic performance analysis. Furthermore, the paper describes how NCA can be integrated into more traditional economic performance measurements, such as the System of National Accounts and their indicators such as adjusted Gross Domestic Product and Genuine Savings. Integration of natural capital into economy-wide analytical frameworks leads to better policy uptake of research findings and it empowers policymakers to avoid short-sighted decisions, which, although they can generate short-term economic gain, can have adverse consequences for economic, social, and environmental sustainability in the long run.
Keywords: C68; E21; E23; E27; Q15; Q18; Q2; Q3; Q5; 330; Natural capital; biodiversity; wealth inequality; ecosystem service; gross domestic product; reforestation; social network analysis